Cellular barcoding identifies clonal substitution as a hallmark of local recurrence in a surgical model of head and neck squamous cell carcinoma - Roh, Vincent; Nowrouzi, Ali; Abdollahi, Amir (Cell reports, 2018)
Local recurrence after surgery for head and neck squamous cell carcinoma (HNSCC) remains a common event associated with a dismal prognosis. Improving this outcome requires a better understanding of cancer cell populations that expand from postsurgical minimal residual disease (MRD). Therefore, we assessed clonal dynamics in a surgical model of barcoded HNSCC growing in the submental region of immunodeficient mice. Clonal substitution and massive reduction of clonal heterogeneity emerged as hallmarks of local recurrence, as the clones dominating in less heterogeneous recurrences were scarce in their matched primary tumors. These lineages were selected by their ability to persist after surgery and competitively expand from MRD. Clones enriched in recurrences exhibited both private and shared genetic features and likely originated from ancestors shared with clones dominating in primary tumors. They demonstrated high invasiveness and epithelial-to-mesenchymal transition, eventually providing an attractive target for obtaining better local control for these tumors.
Gesehen am 16.04.2020